EFFECT OF FERMENTED SOYBEAN MEAL WITH PROBIOTIC AND BETA-GLUCAN ON SOME PRODUCTIVE AND CARCASS TRAITS OF BROILERS - Noora K. Al-Hmedawy; Majid H. Al-Asadi (Chelonian Research Foundation, 2023)
This study aimed the effect of fermented soybean meal with probiotic and beta-glucan on some productive and carcass traits of broiler, from 12/2/2022 to 2/5/2022, at the animal field, College of Agriculture, Basrah University. This study included two stages, the first stage was manufacturing a device for fermenting soybean meal with beta-glucans, to increase its nutritional value, by fermenting the feed with the probiotic on some interactions. The second experiment was the field experiment by rearing broiler chickens. A total of 225 unsexed, one day, broiler Ross 308 chicks were used, were prepared from one of the private hatcheries in Basra Governorate. The chicks were distributed randomly to five treatments, with three replicates (15 chicks per replicate), according to Complete Randomized Design (CRD). The experimental treatments were: T0: (control) basal diet. T1: added soybean meal with 0.5 gm/ kg probiotics (without fermentation) to the basal diet. T2: added soybean meal with 0.5 gm/ kg probiotics + 0.2% beta glucan (without fermentation) to the basal diet. T3: added fermented soybean meal with 0.5 gm/ kg probiotics to the basal diet. T4: added fermented soybean meal with 0.5 gm/ kg probiotics + 0.2% beta glucan to the basal diet. The results of the experiment indicate that there was a significant increased (P≤0.05) for the treatments T3 and T4 on the average final body weight, in weight gain, with a significant decrease (P≤0.05) on the amount of feed intake in T1, T2 and T3 treatments compared with the control treatment (T0). Keywords: Probiotic, fermentation, soybean meal. beta glucan.